Cegah Stunting dengan Pemanfaatan Pangan Lokal - Fajar Andriyani; Nur Khayati, Yulia; Zelda Rizmi Silviana; Hemi Supraptini (Universitas Ngudi Waluyo, 2024)
Stunting is currently the focus of the government in the health status of children as the main indicator in decision making about the quality of public health. Causes of stunting that are often found include lack of knowledge, nutritional intake during pregnancy and after childbirth and limited access to health services obtained, as well as lack of clean water and sanitation facilities. The purpose of community service is to improve mothers' knowledge in making PMT by utilizing local food products to prevent stunting. The Community Service Method will be implemented in 3 stages, namely the First Stage is preparing by conducting a problem assessment and collaborating with partners. The Second Stage is providing counseling on balanced nutrition, using projector media and teaching how to make PMT with direct demonstrations. The Third Stage is conducting an evaluation by interviewing mothers of toddlers. From the results of Community Service, it was found that this activity was attended by 20 mothers of toddlers and 10 cadres. The results showed that there was an increase in the knowledge of mothers of toddlers regarding balanced nutrition and making PMT by utilizing local food products. During the activity, mothers of toddlers seemed enthusiastic and excited. It is hoped that health workers will improve health education to the community, especially in the utilization of local food products to support the growth and development of toddlers and improve public health. Abstrak Stunting saat ini menjadi fokus pemerintah dalam status kesehatan anak menjadi indikator utama dalam pengambilan keputusan tentang kualitas dari kesehatan masyarakat. Penyebab stunting yang sering ditemukan seperti kurangnya pengetahuan, asupan gizi selama kandungan dan setelah melahirkan dan terbatasnya akses layanan kesehatan yang didapatkan, serta kurangnya fasilitas air bersih dan sanitasi. Tujuan pengabdian masyarakat adalah untuk meningkatkan pengetahuan ibu dalam pembuatan PMT dengan pemanfaatan hasil pangan lokal untuk mencegah stunting. Metode Pengabdian Masyarakat akan dilaksanakan dalam 3 tahap yaitu Tahap Pertama melakukan persiapan dengan cara melakukan pengkajian permasalahan dan kerja sama dengan mitra. Tahap Kedua Memberikan penyuluhan mengenai gizi seimbang, menggunakan media proyektor dan mengajarkan pembuatan PMT dengan demonstrasi secara langsung. Tahap Ketiga Melakukan evaluasi dengan cara melakukan wawancara kepada ibu balita. Dari hasil pengabdian Masyarakat didapatkan bahwa kegiatan ini diikuti oleh 20 ibu balita dan 10 kader. Didapatkan hasil bahwa terjadi peningkatan pengetahuan ibu balita mengenai gizi seimbang dan pembuatan PMT dengan pemanfaatan hasil pangan lokal. Selama kegiatan berlangsung ibu balita tampak antusias dan semangat. Diharapkan tenaga kesehatan meningkatkan edukasi kesehatan kepada masayarakat, terutama dalam pemanfaatan hasil pangan lokal untuk menunjang tumbuh kembang balita dan meningkatkan derajat kesehatan masyarakat.